Handgrip Strength As A Screening Tool For Diabetes In Resource-Constrained Settings: A Potential Solution To Overcome Barriers To Diagnosis - Ojulari, Sheriff; Ayinde, Taofeek; Kadir, Riskat Eniola; Sulaiman, Swabirah Enimire (My University, 2023)
Background Information: Diabetes mellitus is an escalating global health concern, especially in low and middle-income countries. Handgrip strength (HGS), a measure of muscle strength, emerges as a potential non-invasive and affordable screening tool for diabetes, particularly in areas with limited healthcare access. Objective: To investigate the relationship between handgrip strength and blood glucose regulation in non-diabetic young adults and to provide valuable insights into the potential of handgrip strength as a preventive and affordable approach to managing diabetes. Methods: A cross-sectional study included 59 University of Ilorin students aged 18-21 in Nigeria. Handgrip strength was measured with a dynamometer, and its links to blood glucose markers (fasting blood glucose, 2-hour post-prandial glucose, and HbA1c) were explored using multiple regression models. Results: Findings revealed significant associations between HGS and glucose regulation markers, particularly FBS, among males. The relationship was evident in females only after adjusting for body mass index (BMI). Furthermore, a notable connection between HGS and 2-hour post-prandial glucose levels was observed in females but not males. However, no significant associations were found between HGS and serum insulin levels across genders. Data availability statement: The data that support the findings of this study are uploaded along with the manuscript.
Keywords: Diabetes Screening Tool; Blood Glucose Regulatory Markers; Handgrip Strength